Investor sentiment, human capital and Fama French factors: measurement and performance in the Malaysian market - Gunathilaka, Chandana; Mohamad Jais (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper examines pricing implications of investors’ behavioral biasness in the Malaysian equity market. By using monthly data from January 2000, through January 2014, we explore the impact of investor sentiment, human capital, and Fama-French risk factors in multiple factor asset pricing models. A unique seven-variable composite index is used for the measurement of investor sentiment. Results indicate that sentiment is a priced risk, and display the ability to capture returns unexplained by SMB (Small minus Big) and HML (High minus Low) factors. Evidence suggests that sentiment is a source of systemic risk, and effectively explains returns of stocks with opaque characteristics. Modeling aggregate labor income produces insignificant results, suggesting that there are no returns for human capital in the Malaysian equity market. The Fama and French three factor model together with investor sentiment risk achieves a substantial pricing efficiency.